Analisis Pengaruh Gaya Kepemimpinan dan Kualitas Sumber Daya Manusaia Terhadap Penerapan Anggraran Berbasis Kinerja - jumame, Manuel (Universitas Sam Ratulangi, 2018)
The result show that there is a significant influence partially between leadership style and implementation of performance budget also there is a significant influence partially between human resources quality and implementation of performance budget.Keywords: leadership style, human resources quality, implementation of performance budget.